Yhteisopettajuus liikunnan opetuksessa. 7-luokkalaisten ja heidän opettajiensa kokemuksia yhteisopettajuudesta - Juga, Emma (2025)
Juga, E. 2025. Co-Teaching in Physical Education: Experiences of 7th-Grade Students and Their Teachers. Faculty of Sport and Health Sciences, University of Jyväskylä, Master’s Thesis in Sport Pedagogy, 33 pages, 4 appendices.